2016
DOI: 10.1071/an14962
|View full text |Cite
|
Sign up to set email alerts
|

Ergovaline, an endophytic alkaloid. 1. Animal physiology and metabolism

Abstract: Abstract. Ergovaline is an ergot alkaloid found in some endophyte-infected ryegrasses and it has been implicated in the expression of ergotism-like symptoms of grazing livestock, as well as in the protection of the plant against invertebrate predation and abiotic stresses. These selection pressures have resulted in a conflict between the needs of the pasture for persistence and the needs of the animal for production. Ergovaline has not been well studied in terms of animal physiology until recently. There are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 103 publications
0
17
0
1
Order By: Relevance
“…Consumption of ergot alkaloids by cattle is known to constrict the caudal artery (Aiken et al, 2007), right ruminal artery and vein (Foote et al, 2011), and mesenteric artery and vein (Jia et al, 2015). Ergot alkaloid-induced vasoconstriction is thought to be a contributor to several symptoms of fescue toxicosis (Klotz and Nicol, 2016). Therefore, the caudal artery luminal area was determined in this study as a parameter to assess potential Se-form treatment differences.…”
Section: Caudal Artery Area and Animal Performance Were Not Affected mentioning
confidence: 99%
“…Consumption of ergot alkaloids by cattle is known to constrict the caudal artery (Aiken et al, 2007), right ruminal artery and vein (Foote et al, 2011), and mesenteric artery and vein (Jia et al, 2015). Ergot alkaloid-induced vasoconstriction is thought to be a contributor to several symptoms of fescue toxicosis (Klotz and Nicol, 2016). Therefore, the caudal artery luminal area was determined in this study as a parameter to assess potential Se-form treatment differences.…”
Section: Caudal Artery Area and Animal Performance Were Not Affected mentioning
confidence: 99%
“…Concerns of the alkaloids manifest with reduced blood flow to the periphery, reduced reproductive efficiency, and reductions in growth performance [ 2 4 ]. Of the alkaloids associated with endophyte-infected tall fescue, ergovaline is the most predominant of concern in the plant, as it imposes the greatest detrimental effects on livestock [ 5 , 6 ]. Reducing the consumption of endophyte-infected tall fescue has proven to be a challenge for livestock producers, as it occupies roughly 15 million hectares in the United States [ 7 ], with the majority in the east and southeast regions of the country.…”
Section: Introductionmentioning
confidence: 99%
“…Structurally, ergot alkaloids are similar to biogenic amines, such as 5-HT, which allows them to act as agonists or antagonists (Berde, 1980) and bind to serotonergic receptor sites (Eckert et al, 1978). There are 14 different receptor subtypes of 5-HT (Hoyer et al, 1994;Klotz and Nicol, 2016) that could elicit different responses when exposed to various ergot alkaloids. Dyer (1993) showed that 5-HT 2 receptors are involved in vasoconstriction by ergovaline (ERV) and Schöning et al (2001) demonstrated that the vasoconstrictive effect of ERV is due to 5-HT 2A activation in rat and guinea pig arteries.…”
Section: Introductionmentioning
confidence: 99%